Halitose: limitando a qualidade de vida - Domingos, Patricia Aleixo dos Santos (2011)
The aim of this literature review is to observe the causes, symptoms and consequences of halitosis and the influence of preventive measures. Halitosis has multifactorial causes, and may have local and systemic origins. It can limit the quality of life of individuals and often occurs due to lack of knowledge of prevention methods. Therefore, it is important that professionals are better prepared and people informed about the physiological and pathological halitosis to prevent its individual and social effects.